The Power of Relational Algebraic Thinking: a Study of Relational Thinking in Grade 8 in Banda Aceh - . Mailizar (Jurnal Peluang, 2012)
AbstractAlgebra is a gateway of technology improvement. It needs students to have good relational thinking in order for algebraic understanding to grow.  Relational thinking means that the students develop the concept of a number that can vary, build upon similarities and differences, and appreciate for the equals sign as signifying equivalence of expressions. Three categories of relational thinking will be discussed in this paper: emerging, consolidating and established relational thinking. Analyzing data from some junior high school students in Banda Aceh it can be said that most students are still at the stage of emerging relational thinking. They construct limited responses to given questions. Many consolidating relational thinkers’ students are concerned that the relationships hold only for a specific range of numbers. Established relational thinkers demonstrate good algebraic thinking processes. Three types of sentences have a potential for develop algebraic thinking with respect to equivalence, attention to operations, different numbers, compensation, and generalisation. Having presented students’ responses to these three types of questions, we ask: how can teachers help students to move beyond the partial descriptions that characterize emerging relational thinkers. Key words: Relational thinking, emergent, consolidating, and established